URGENSI PENDIDIKAN SEKSUAL DI ERA MODERN: ANALISIS KONSEPTUAL QS AN-NUR AYAT 30-33 DAN 58 - Nabil Tito Prasetyo; Muhammad Akmansyah; Amirudin, Ahmad Fatoni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The modern era is characterized by rapid and diverse access to information, including sexual content thatdoes not always align with Islamic moral values. In this context, sexual education is urgently needed to shape a physically, mentally, and spiritually healthy generation. This article conceptually examines the urgency of sexual education based on verses 30, 33, and 58 of the Quran. Using textual interpretation, analysis of moral educational values, and practical application, this study concludes that both verses contain principles that support ethical and preventative Islamic sexual education. Recommendations are provided forfamilies, educational institutions, and public policy to integrate sexual education into contemporary Islamic education.